Distribution Study of 5-[5-(trifluoromethyl)-1,2-oxazole-3-yl]-furan-2-sulfonamide and Its Metabolites in Rats - I. I. Yaichkov; A. L. Khokhlov; M. K. Korsakov; N. N. Volkhin; S. S. Petukhov; O. E. Lazariants; A. V. Korovina (Регуляторные исследования и экспертиза лекарственных средств, 2025)
INTRODUCTION. This article continues a series of publications on the pharmacokinetics of 5-[5-(trifluoromethyl)-1,2-oxazole-3-yl]-furan-2-sulfonamide (TFISA), a novel compound for the treatment of open-angle glaucoma. The distribution of TFISA and its metabolites in rat organs and tissues has not been previously studied in preclinical trials.AIM. This study aimed to assess the tissue distribution and bioavailability of 5-[5-(trifluoromethyl)-1,2-oxazol-3-yl]-furan-2-sulfonamide and its metabolites in rat organs and tissues and to validate the analytical procedures developed for this purpose. MATERIALS AND METHODS. The study used 60 male Wistar rats. TFISA was administered by bilateral ocular instillation of 1% ophthalmic suspension at a dose of 40 μL (approximately 3.7 mg/kg). Tissue samples (liver, kidney, lung, brain, heart, spleen, skin, muscle tissue, and eyes) were collected 1, 2, 4, 8, 12, 24, 48, 72, 144, and 216 h after instillation (from 6 rats at each time point). The samples were immediately homogenised using methanol and were stabilised with ascorbic acid solutions. High-performance liquid chromatography with tandem mass spectrometric detection was used to quantify TFISA, N-hydroxy-5-[5-(trifluoromethyl)-1,2-oxazole-3-yl]furan-2-sulfonamide (M1), and N-acetyl-5-[5-(trifluoromethyl)-1,2-oxazole-3-yl]-furan-2-sulfonamide (M2) in homogenised organ and tissue samples.RESULTS. This study involved full validation of the analytical procedures developed for the quantitative determination of TFISA and its metabolites, which was conducted separately for eye tissues and other biological samples. The tissue bioavailability (ft) of TFISA decreased from 13.0 to 0.7 in the following order: eye tissues (administration and action site) > spleen > lungs ≥ heart ≥ liver > kidneys > brain > skin ≥ muscles. The ft values for M1 decreased from 52.0 to 2.5 in the following order: spleen ≥ lungs ≥ heart ≥ liver > kidneys > brain > muscles ≥ eye tissues > skin. The ft values for M2 were lower than those for TFISA and M1 and decreased from 6.4 to 0.3 in the following order: liver ≥ kidneys > heart > lungs > eye tissues > skin > spleen ≥ muscles > brain.CONCLUSION. The validated bioassays have been successfully applied to study the distribution of TFISA and its metabolites in male rats. TFISA best penetrates into the eyes and well-vascularised organs. M1 is highly bioavailable in the spleen, heart, and lungs. M2 shows the highest bioavailability in the liver and kidneys of rats.